VARIABEL-VARIABEL PEMBEDA RASIO KECUKUPAN MODAL BANK PERKREDITAN RAKYAT (BPR) DI BALI - Susilowati, Ni Made Novi; Purbawangsa, Ida Bagus Anom; Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.06.TAHUN 2017, 2017)
The study aimed to determine whether the size, the loan to deposit ratio (LDR), the cash ratio (CR), the non-performing loan (NPL), the equity to total liabilities ratio, the return on assets (ROA), the net interest margin ( NIM) and BOPO can distinguish the rate of bank capital adequacy and to determine the dominant financial ratios that distinguish the ratio of capital adequacy of banks. The number of samples was 102 of rural banks/BPR in Bali Province which was determined by purposive sampling method. The data analysis used discriminant analysis with simultaneous estimation method. The results showed that eight independent variables can jointly be used to distinguish the level of capital adequacy ratio of the BPR but only six (6) independent variables which were partially rated to be significantly differentiate the levels of capital adequacy of the bank, including the size, LDR, CR, NPL, EQTL, and NIM. The dominant financial ratio that can distinguish the level of capital adequacy of banks was the NPL. Discriminant model is useful for predicting the position of the CAR of banks in the industry, so that the management can more effectively manage the capital adequacy to anticipate changes in the business environment of banks.
Keywords: capital adequacy ratio, financial ratios